2016
DOI: 10.1108/jcs-10-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Implementing yoga within the school curriculum: a scientific rationale for improving social-emotional learning and positive student outcomes

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:368933 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 131 publications
3
67
0
1
Order By: Relevance
“…Yoga is a comprehensive system of practices for physical and psychological health and well-being that typically incorporates four techniques: physical postures/exercises to promote strength and flexibility, breathing exercises to enhance respiratory functioning, relaxation strategies that focus on reducing tension and stress, and meditation/mindfulness practices to enhance mind–body awareness and improve attention and emotion regulation skills (Butzer et al 2016). As a common component of yoga practices, mindfulness techniques typically involve cultivating a non-judgmental and non-reactive state of awareness by continually bringing one's attention to the present moment (Carim-Todd et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoga is a comprehensive system of practices for physical and psychological health and well-being that typically incorporates four techniques: physical postures/exercises to promote strength and flexibility, breathing exercises to enhance respiratory functioning, relaxation strategies that focus on reducing tension and stress, and meditation/mindfulness practices to enhance mind–body awareness and improve attention and emotion regulation skills (Butzer et al 2016). As a common component of yoga practices, mindfulness techniques typically involve cultivating a non-judgmental and non-reactive state of awareness by continually bringing one's attention to the present moment (Carim-Todd et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a qualitative study of a school-based yoga intervention, Conboy et al (2013) found that students often reported health behavior changes resulting from the intervention, despite the fact that the intervention did not provide specific recommendations regarding health behavior. It is possible that these behavioral changes occurred as a result of increased mind–body awareness, which may have caused participants to gravitate toward healthy behaviors and away from unhealthy behaviors, based on an increased awareness of how these behaviors make the individual feel (Butzer et al 2016). Accordingly, a number of substance abuse treatment programs have incorporated yoga or meditation as contributing therapies, and there is some research demonstrating efficacy of such treatments for adults (Carim-Todd et al 2013; Hallgren et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to specifically investigate student perceptions of school-based yoga given that, in addition to incorporating aspects of mindfulness and/or meditation, yoga differs from conventional mindfulness-based programs in that yoga also includes physical postures and breathing exercises (Butzer, Bury, Telles & Khalsa, 2016). In addition, the majority of qualitative studies of school-based yoga have been conducted on high school students (Conboy et al, 2013; Miller et al, 2014; Wang & Hagins, 2016) and elementary school students (Case-Smith et al, 2010; Dariotis et al, 2016a; Dariotis et al, 2016b; Dariotis et al, 2017; Finnan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [6] have been limited by lack of objective measurement and randomization, factors which may be limited in generalizability and acceptance. Schools present a lucrative opportunity for yoga intervention programs [7], and schools can implement changes that affect physical education and the acceptability of healthy behaviors. Results suggest that schoolbased yoga programs may be appropriate for promoting healthy behaviors [8].…”
Section: Introductionmentioning
confidence: 99%